Boosting Students' Mathematical Problem-Solving Skills with PBL-Based LiveWorksheets: Focus on Whole Numbers and Fractions Topic - Usqo, Urwatil; Hutapea, Nahor Murani; Kartini, Kartini (Edumatika, 2024)
Problem solving skills is one of the important skills that students must master through learning mathematics. One alternative to improve students' mathematical problem-solving skills is using the Problem-based Learning (PBL) learning model combined with technology-based learning media. This research aims to produce PBL-based electronic student worksheets (e-worksheets) on the topic of whole numbers and fractions that are valid, practical and effective to improve students' mathematical problem-solving skills. The development of e-worksheets uses a 4D development model involving seventh-grade students from one of the junior high schools in Rokan Hulu, Riau, Indonesia as field test subjects. The results of data analysis show that the e-worksheet developed using LiveWorksheet application has met the valid criteria based on experts judgement and practical based on the practicality questionnaires. E-worksheets have also been proven effective in improving students' mathematical problem-solving skills with an average N-gain at high criteria.